The Analysis of Students’ Difficulties in Using Computer Terms - Ika Swantika; Refin Harissandi; Rossya Diva Anwar (PT FORMOSA CENDEKIA GLOBAL, 2023)
Computer is used for many purposes especially for improving and supporting in education system. Students can operate computer as well as possible, but most of them don’t know the meaning of some terms in computer science. The aims of this study are to investigate the Students’ difficulties in Using Computer Science Terms at STMIK Pelita Nusantara, then to explore the students’ difficulties in Using Computer Science Terms at STMIK Pelita Nusantara. This is a qualitative research. The participants of this study were students of second semester of STMIK Pelita Nusantara. The total of students were 35 students that consist of 17 males and 18 females. The result showed that computer terminology is the one problem that the students face. The lack of vocabulary become the main reason why the students cannot use the terms well. Students’ obstacles were not only in mastering vocabulary but also in mastering the translation in using computer terms. Sometimes the students know the usage of computer terms but they don’t know the meaning of them.